Dr Daing reappointed UMP vice-chancellor - UMP, LIB (The Star Publications (M) Berhad, 2017)
KUANTAN: Professor Datuk Dr Daing Nasir Ibrahim has been reappointed as vice-chancellor of Universiti Malaysia Pahang (UMP) for another two years.